Abrasive wear behavior of functionally graded Al3Ti reinforced aluminum matrix composite - Yildiz, Eylul Tugce Yaman; Savas, Omer; Baser, Muhammed Soner; Kocaman, Engin (SPRINGER SINGAPORE PTE LTD, 2025)
Aluminum alloys are widely used in industry due to their light weight. These alloys are generally exposed to abrasive wear, which diminishes their effective lifespan. The wear resistance of these alloys is enhanced by adding various reinforcements, however, this enhancement comes at the cost of reduced fracture toughness. This paradox of increased wear resistance versus decreased fracture toughness in aluminum alloys can be resolved by using functionally graded materials (FGMs). This study focuses on the abrasive wear behavior of functional graded aluminum matrix composites reinforced with Al3Ti particles. The wear properties of the composites were investigated by considering the characteristics of the composite such as matrix type and various composite zones, as well as the wear parameters such as abrasive particle diameter, load, sliding speed and distance. Taguchi method was used in the abrasive wear tests in order to get more reliable results in a time-efficient manner. Experiment recipes were created based on the L-27(6(3)) orthogonal series. As a result of the study, it is observed that the wear resistance of the composites increases with an increase in Al3Ti reinforcement content and hardness of the matrix. In addition, the size of abrasive particles and the applied load are significant factors affecting abrasive wear.
Keywords: functionally graded; Al3Ti; Taguchi; abrasive wear; MECHANICAL-PROPERTIES; SITU; FABRICATION; ALLOY; PARTICLE; MICROSTRUCTURE; OPTIMIZATION; Metallurgy & Metallurgical Engineering